Quantum Tunneling of Josephson Vortices in High-Impedance Long Junctions - Micha Wildermuth, Matthias (Experimental Condensed Matter Physics, 2023)
In the last decades, superconducting devices have emerged as a promising platform for quantum technologies, including quantum sensing and quantum computing. Their key elements are Josephson junctions, which allow for coherent supercurrent tunneling between two weakly linked superconductors. If such a junction is extended in one direction to a long junction, the superconducting phase difference can vary in space and time and may allow for quantized phase windings that drive supercurrent vortices.